The Association of the Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, Lymphocyte-to-Monocyte Ratio and Systemic Inflammation Response Index with Short-Term Functional Outcome in Patients with Acute Ischemic Stroke - Zhang YX; Shen ZY; Jia YC; Guo X; Guo XS; Xing Y; Tian SJ (Dove Medical Press, 2023)
Ya Xin Zhang,1- 3,* Zhi Yuan Shen,1- 3,* Yi Cun Jia,1- 3 Xin Guo,1- 3 Xiao Su Guo,1- 3 Yuan Xing,1- 3 Shu Juan Tian1- 3 1Department of Neurology, The First Hospital of Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China; 2Department of Neurology, Hebei Hospital, Xuanwu Hospital, Capital Medical University, Shijiazhuang, Hebei, People's Republic of China; 3Neuromedical Technology Innovation Center of Hebei Province, Shijiazhuang, Hebei, People's Republic of China*These authors contributed equally to this workCorrespondence: Shu Juan Tian; Yuan Xing, Department of Neurology, The First hospital of Hebei Medical University, Shijiazhuang, Hebei, 050030, People's Republic of China, Email jtian72@126.com; leaf_trunks@163.comBackground and Purpose: The aim of this study was to explore the relationship between functional prognosis and the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR) and systemic inflammatory response index (SIRI) in patients with acute ischemic stroke (AIS) at discharge.Methods: A total of 861 patients with AIS were enrolled between January 2019 and December 2021. Blood cell counts were collected on admission. Logistic regression analysis was performed to assess the relationship between NLR, PLR, LMR, SIRI and adverse functional outcomes (modified Rankin scale score of 3- 6) at discharge. We also used receiver operating characteristic (ROC) curves to estimate the overall ability of NLR, PLR, LMR and SIRI to judge short-term functional outcomes. Associations between NLR, PLR, LMR, and SIRI with length of hospital stay were analyzed by Spearman correlation test.Results: A total of 194 patients (22.5%) had poor functional outcomes at discharge. Multivariate logistic regression analysis showed that NLR (odds ratio [OR], 1.060; 95% confidence interval [CI] 1.004- 1.120, P=0.037), PLR (OR, 1.003; 95% CI 1.000- 1.005, P=0.018), LMR (OR, 0.872; 95% CI 0.774- 0.981, P=0.023) and SIRI (OR, 1.099; 95% CI 1.020- 1.184, P=0.013) were independent factors for poor functional outcome. The odds ratios of the highest versus lowest quartiles of NLR, PLR and SIRI were 2.495 (95% CI 1.394- 4.466), 1.959 (95% CI 1.138- 3.373) and 1.866 (95% CI 1.106- 3.146), respectively. The odds ratio of the lowest versus highest quartile of LMR was 2.300 (95% CI 1.331- 3.975). The areas under the curve (AUCs) of the NLR, PLR, LMR, and SIRI to discriminate poor functional prognosis were 0.644, 0.587, 0.628, and 0.651, respectively. NLR, LMR, and SIRI were related with the length of hospital stay (P< 0.05).Conclusion: NLR, PLR, LMR, and SIRI were associated with functional outcome at discharge in AIS patients. NLR, LMR and SIRI were related to hospitalization days in patients with AIS.Keywords: acute ischemic stroke, short-term functional outcome, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, systemic inflammatory response index